Heat pumps technology in Ukraine. Situation and perspective evolution - Dolinskiy, A.; Basok, Boris; Nedbailo, Alexander; Tkachenko, M. (My University, 2013)
The main destroyer of centralized systems heating from 2015, probably will be no individual boiler and heat pump. It is destined to put this technology cross on the direct combustion of fuel for heating. how the internal combustion engine at the time was replaced by steam engine, so heat pumps out of the market today various boilers.
Keywords: тепловий насос; heat pump; кафедра теплоенергетики та холодильної техніки